Association between inflammation, lipopolysaccharide binding protein, and gut microbiota composition in a New Hampshire Bhutanese refugee population with a high burden of type 2 diabetes - Moser, Brandy; Moore, Dustin; Khadka, Bishnu; Lyons, Carrie; Foxall, Tom; Andam, Cheryl P.; Parker, Cooper J.; Ochin, Chinedu; Garelnabi, Mahdi; Sevigny, Joseph; Thomas, W. Kelley; Bigornia, Sherman; et al. (Frontiers in Nutrition, 2023)
South Asian refugees experience a high risk of obesity and diabetes yet are often underrepresented in studies on chronic diseases and their risk factors. The gut microbiota and gut permeability, as assessed through circulating lipopolysaccharide binding protein (LBP), may underlie the link between chronic inflammation and type 2 diabetes (T2D). The composition of the gut microbiota varies according to multiple factors including demographics, migration, and dietary patterns, particularly fiber intake. However, there is no evidence on the composition of the gut microbiota and its relationship with metabolic health in refugee populations, including those migrating to the United States from Bhutan. The objective of this study was to examine glycemic status in relation to LBP, systemic inflammation fiber intake, and gut microbiota composition in Bhutanese refugee adults residing in New Hampshire (n=50). We identified a substantial chronic disease burden in this study population, and observed a correlation between glycemic status, LBP, and inflammation, and a correlation between glycemic status and gut microbiome alpha diversity. Further, we identified a correlation between proinflammatory taxa and inflammatory cytokines. Short-chain fatty acid (SCFA)-producing taxa were found to be inversely correlated with age, while proinflammatory taxa were found to increase. The findings of this study highlight areas for future investigations of inflammation and glycemic impairment, in addition to informing potential future interventions targeting this vulnerable population.